Impact of drying and extraction method on antioxidant capacity, phenolic compounds and betalain pigment of alternanthera sessilis red - Shaharuddin, Syafiqah; Othman, Azizah; Ismail, Amin (CSIR-National Institute of Science Communication and Policy Research (NIScPR), 2023)
This study attempts to determine the effect of drying and extraction methods on the antioxidant capacity, phenolic compounds, and betalain pigment of Alternanthera sessilis red. Evaluation of extraction yield showed that superheated steam drying exhibited a higher yield than freeze drying. A combination of superheated steam drying and ultrasonic-assisted extraction resulted in the highest 2,2-Diphenyl-1-picrylhydrazyl radical scavenging activity (39.48%). Ferric reducing antioxidant power analysis revealed that ultrasonic-assisted extraction enhanced the antioxidant capacity (878.86 mg Trolox equivalents/100g dried sample) of freeze-dried Alternanthera sessilis red on par with superheated steam dried sample. The increase in the concentration of major phenolic compounds was also reported in all superheated steam drying samples (gallic acid: 1556.98 -1715.75 mg/100 g dried sample; vanillic acid: 217.21 - 230.41 mg/100 g dried sample; p-coumaric acid: 1422.10 – 1559.96 mg/100 g dried sample). As for betalain pigment, superheated steam drying caused its degradation but the impact was reduced after combination with ultrasonic-assisted extraction (betanin : 9.77 mg/100 g dried sample; betaxanthin: 9.07 mg/100 g dried sample). The present result showed that superheated steam drying enhanced the extraction yield, antioxidant capacity and concentration of phenolic compounds of Alternanthera sessilis red, regardless of the extraction method.